Flight control for advanced supersonic transport aircraft handling quality design - Steer, A. J. (Cranfield University, 2001)
Concorde's unique low-speed handling qualities are acceptable when flown in a rigidly procedural manner by experienced pilots. However, to be commercially viable and environmentally acceptable more numerous second generation supersonic transport (SST) aircraft would have increased passenger carrying capacity, range and the flexibility to integrate with sub-sonic air traffic. Their much larger size, weight and inertia compared to Concorde's, combined with increasing levels of relaxed longitudinal stability to improve aerodynamic efficiency, results in unstable dynamics and degraded handling qualities on the final approach, where precise manual flightpath control is required. Modern fly-by-wire command and stability augmentation systems can restore stability, provide task tailored command laws and an associated level of handling qualities. Nonlinear Dynamic Inversion (NDI) enables control law prototyping and analysis for the rapid assessment, of conceptual designs to identify control power and command response requirements using both off-line and real-time simulation. This study has developed and applied NDI, and its realisable form (RNDI), in a novel way to design flight control laws specifically addressing handling quality requirements using selected criteria. Piloted validation has demonstrated that NDI pitch rate command will consistently provide Level 1 low-speed handling qualities in both steady and turbulent conditions. However, the best handling qualities can be achieved through a second order pitch rate response, generated by pre-filters, designed to author-suggested constraints on control anticipation parameter (CAP). The SST pitch rate criterion envelope, modified to ensure positive pitch attitude dropback, can then be applied to verify the time response. The resulting pre-filters are easily applied to RNDI inner loop controllers and would be straightforward to implement with simple and proven sensor requirements. Carefully designed NDI normal acceleration command laws are also capable of generating Level 1 low-speed handling qualities in steady conditions. However, their degraded performance in turbulence was exacerbated, relative to the pitch rate command laws, by the use of a fixed base simulator for pilot evaluation. Further motion based simulation studies would provide, in addition to pitching motion, the normal acceleration response cues necessary for a fair command law comparison to be made.